2005
DOI: 10.1111/j.1365-2125.2005.02538.x
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective disposition of fluoxetine and norfluoxetine during pregnancy and breast‐feeding

Abstract: AimsTo compare the disposition of fluoxetine and norfluoxetine enanantiomers in the mother, foetus and infant. MethodsBlood from pregnant women taking fluoxetine ( n = 9), during pregnancy was sampled in the third trimester and at delivery (maternal and cord venous blood), and from the infants 48 h after delivery. The subset of these women who were breastfeeding, plus additional subjects recruited in the postpartum period, were studied further, and maternal and infant blood, and breast milk was sampled between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
104
2
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 128 publications
(117 citation statements)
references
References 31 publications
6
104
2
5
Order By: Relevance
“…These include pharmacological factors related to varying half lives, pharmacologically active metabolites 31 and possible competitive inhibition with other medications. 11 Paroxetine's high potency for inhibition of 5HT reuptake and affinity for muscarinic receptors may lead to adverse neonatal outcomes once medication exposure ceases, suggesting a 'discontinuity condition' as proposed by Moses-Kolko.…”
Section: Discussionmentioning
confidence: 99%
“…These include pharmacological factors related to varying half lives, pharmacologically active metabolites 31 and possible competitive inhibition with other medications. 11 Paroxetine's high potency for inhibition of 5HT reuptake and affinity for muscarinic receptors may lead to adverse neonatal outcomes once medication exposure ceases, suggesting a 'discontinuity condition' as proposed by Moses-Kolko.…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding of similar neuroanatomical and functional consequences in humans is limited. Because SRIs readily cross the placenta and the blood-brain barrier (19), concerns have been raised about the developmental consequences of altered fetal 5-HT signaling (12,20) or other downstream consequences (21) following prenatal SRI exposure. Importantly, antenatal maternal mood disturbances also have adverse consequences on later cognitive and language development (22)(23)(24) and affect early 5-HT levels (25), leading to confusion about how to distinguish the developmental impact of SRIs from antenatal maternal mood disturbances.…”
mentioning
confidence: 99%
“…There is a stereoselective disposition of fluoxetine and norfluoxetine resulting in increased concentrations of the biologically active enantiomers in the infant compared with the mother [31]. In a study including eleven infants exposed to fluoxetine through breast milk it was reported a variation in platelet serotonin levels in one infant but no adverse effects were observed [32].…”
Section: Fluoxetinementioning
confidence: 99%